Marine Heatwave, Harmful Algae Blooms and an Extensive Fish Kill Event During 2013 in South Australia - Roberts, Shane D.; Van Ruth, Paul D.; Wilkinson, Clinton; Bastianello, Stella S.; Bansemer, Matthew S. (Frontiers in Marine Science, 2019)
In 2013, South Australia experienced unusually high and variable water temperatures (5°C above the historic average), with a peak sea surface temperature of approximately 27°C over a wide geographic area covering both gulfs and shelf waters. Over the same period and similar geographic area, a prolonged and widespread marine mortality event occurred. From January to May 2013, low level rates of incidental morbidity and mortality of abalone (Haliotis rubra and H. laevigata) and at least 29 fish species were observed. Mortalities were geographically extensive from Port MacDonnell on the South Coast of South Australia to Point Drummond on Eyre Peninsula, and including two gulf systems, spanning approximately 2,900km of coastline. Mortalities were investigated using gross pathology, histopathology, bacterial culture and polymerase chain reaction (PCR) techniques. Water samples were collected to assess water column nutrient status and phytoplankton biomass levels and community composition. High nutrient concentrations were suggestive of high phytoplankton productivity, with conditions conducive to diatom blooms. A harmful (abrasive) diatom, Chaetoceros coarctatus, was observed in higher concentrations than the historical average. Observed fish mortalities were restricted to a small proportion of the populations and primarily comprised of temperate small-bodied benthic inshore species. Fish histopathology was suggestive of prolonged stress (melanomacrophage aggregation in spleens and kidneys), physical gill damage (focal gill lesions likely caused by C. coarctatus) and lethal bacterial septicaemia. Infectious and notifiable diseases were ruled out in all fish and abalone samples. Abalone mortalities were also restricted to a small proportion of the population with thermal stress a likely contributing factor that resulted in terminal secondary bacterial infections. A marine heatwave event, which promoted blooms of algae, including C. coarctatus, was likely the primary cause of widespread marine mortalities throughout South Australia in 2013. With marine heatwaves projected to increase in frequency, duration and spatial extent, this investigation demonstrated that most at risk will be temperate species in shallow water habitats already at their upper thermal tolerance limits, particularly those with high site fidelity. This should be considered in future climate proofing strategies, including risk and impact assessments underpinning the management of marine resources, fisheries, aquaculture and ecotourism.